March for Life as Specific Example of a Postsecular Conflict? - Ludmila Böhmová (Gender a Výzkum, 2022)
The conflict between the pro-life and pro-choice movements over the question of the right to abortion can be assigned to the category of a (global) cultural war. Croatia is a region where significant desecularisation tendencies can be observed, and where there has been a return of religion into the public space. It is a region in which the Roman Catholic Church and the conservative movement intervene in the debates on the right to abortion and tend to shape the public discourse on this issue. The article responds to the debate about the existence of culture wars in the Croatian context. To establish the Croatian context of this situation, the text uses the concept of a'postsecular conflict' as defined by Kristina Stoeckl, who uses this term instead of the term 'culture war'. The research is based on a content analysis of newspaper articles published in five different periodicals between 2016 and 2020 that all explicitly mention the March for Life in Zagreb. This is not the case of a Western concept being mechanically applied in a different non-Western context. The article transposes the concept of a postsecular conflict to the context of a country in which there is one dominant religious actor that intervenes in society. In the case of Croatia and other countries like this, the conflict between the pro-life and pro-choice movements plays out not only on the conservative-liberal line but also the religious-secular one.